The deposits channel revisited. (7th September 2021) - Schaffer, Matthew; Segev, Nimrod
Summary: Drechsler et al. (2017) present a novel reformulation of the bank lending channel of monetary transmission based on market power in local deposits markets, which they term the deposits channel. In this paper, we first perform a successful narrow replication of their key empirical results. We then revisit their results on lending in two ways. First, recent studies have pointed out the unique dynamics of credit card loans in Community Reinvestment Act loan origination data. When accounting for this heterogeneity, we find key results are sensitive to the inclusion of credit card banks that raise funds outside of local deposit markets. Second, we show that inconsistencies with related empirical studies can be explained by differences in market power measure, sample period, and the inclusion of alternative control variables. The results highlight that market power on opposing sides of bank balance sheets can impact monetary transmission through alternative channels. Overall, this paper suggests the mechanisms underlying the response of lending to monetary policy remains an important open question.